Not Only Digital: A Review of ACM's Early Involvement with Analog Computing Technology. - Care, Charles (Communications of the ACM, 2007)
The article presents a review of the Association for Computing Machinery's (ACM) early involvement in analog computing. Analog computing, a class of computing machinery that encouraged an experiment-oriented relationship between human and computer, was abandoned in favor of digital computing because of general trends and preferences within the field of computer science. The author examines the analog computer's perception within the ACM as digital technology became more established, focusing on the 1950s and 1960s.